2015
DOI: 10.1002/srin.201400332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cerium on Characteristic of Inclusions and Grain Boundary Segregation of Arsenic in Iron Melts

Abstract: In order to depress the embrittlement induced by grain boundary segregation of arsenic in steel, the effect of Ce addition on the formation of arsenious inclusions and arsenic concentration at grain boundaries were systematically investigated in iron melts. The results showed that different types of arsenious rare earth inclusions were formed with different Ce content. As Ce content increased from 0.037 to 0.095 wt%, the dominant inclusion in the melt was changed from the Ce-S-O inclusion fully coated by Ce-S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…RE 2 O 3 , RE 2 O 2 S, and RES are possible oxides, sulfides, and oxysulfides, respectively. For the arsenic ones, CeAs and LaAsO 4 were identified [3,25,28]. The remaining ones, however, have not been identified yet.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…RE 2 O 3 , RE 2 O 2 S, and RES are possible oxides, sulfides, and oxysulfides, respectively. For the arsenic ones, CeAs and LaAsO 4 were identified [3,25,28]. The remaining ones, however, have not been identified yet.…”
Section: Introductionmentioning
confidence: 96%
“…These elements are very hard to remove during the mainstream steelmaking process. Arsenic is easy to segregate to phase and grain boundaries in the solidification, heat treatment, oxidation, and cooling process [3][4][5][6]. These arsenic-rich grain boundaries are potential crack sources under high temperatures because of the low melting point of arsenic, and the segregation of arsenic significantly reduces the binding force of grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…13,14) It was proved that RE-As even RE-O-S-As inclusions might form in arsenic RE steels. 15,16) What kinds of inclusions may form greatly depends on the chemical compositions of steel, especially the concentrations of RE, O and S; further, the formation of arsenic inclusions depends to a large extent on RE inclusions. It was reported that arsenic existed as many kinds of inclusions in steel, such as RES•AsS, 16) RE-As or RE-O-As 17) and RE-As-P. 18) However, the formation mechanism of RE inclusions is still controversial for the lack of thermodynamic data, especially for arsenic inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic has an adverse effect on steel; for instance, the surface hot shortness increases, and the reduction of area and impact toughness decrease with the increase of arsenic content in steel [3][4][5][6]. Under the hot rolling or welding conditions, the arsenic in the steel leads to the increase in the content of arsenic at grain boundaries and the expansion of welding cracks [4,[7][8][9]. Moreover, as the oxidability of arsenic is less than that of iron, it is difficult to remove arsenic by oxidation in the ironmaking or steelmaking process.…”
Section: Introductionmentioning
confidence: 99%